Confidentiality and the ethics of medical ethics. Issue 4 (20th August 2003) - Rogers, W A; Draper, H
Abstract : In this paper we consider the use of cases in medical ethics research and teaching. To date, there has been little discussion about the consent or confidentiality requirements that ought to govern the use of cases in these areas. This is in marked contrast to the requirements for consent to publish cases in clinical journals, or to use personal information in research. There are a number of reasons why it might be difficult to obtain consent to use cases in ethics. Many cases concern people who are incompetent, and thus unable to give consent. Often the material is of a sensitive nature, it is not clear who should give consent, or the ethicist has no access to those involved. We argue that the use of cases in ethics research and teaching can be justified by appeal to the public interest argument, and suggest a number of areas for discussion and clarification.